Alasan Pembenar Korban yang Melakukan Tindak Pidana Perspektif Teori Pertanggungjawaban Pidana - Justika Hairani; Ali Masyhar; Cahya Wulandari (Pusat Riset dan Inovasi Nasional, 2025)
This article explores the concept of justifying grounds (alasan pembenar) in the context of victims who commit criminal acts, analyzed through the lens of criminal liability theory. Under Indonesian criminal law, criminal liability requires the existence of an unlawful act; however, certain conditions may negate the unlawful nature of such acts, one of which includes justifying grounds. The focus of this article is to examine situations in which victims engage in criminal behavior as a response to threats or assaults they have experienced, such as in cases of self defense or coercion. The research employs a normative legal approach by analyzing statutory regulations and legal doctrines. The findings indicate that the application of justifying grounds can exempt victims from criminal liability if their actions meet specific criteria outlined in the Indonesian Penal Code (KUHP), particularly Articles 48 and 49. The article underscores the importance of a contextual approach in the application of criminal law and highlights the need for caution among law enforcement authorities when evaluating cases in which victims become perpetrators, in order to uphold justice and ensure balanced legal protection.